Marine debris surveys on four beaches in Rizhao City of China - C. Zhou; X. Liu; Z. Wang; T. Yang; L. Shi; L. Wang; L. Cong; X. Liu; J. Yang (Global Journal of Environmental Science and Management)
Compared with USA, UK, Brazil, Indonesia, Australia, etc., marine debris research in China has received less attention and few studies have attempted to quantify the abundance and mass of marine debris. In this paper, the abundance, composition and source of beached marine debris, and debris collection system and frequency as well as dustbins’ conditionwere investigated in Duodaohai, Wanpingkou, Shanhaitian and National Forest Park beaches of Rizhao City from June 1 to 10, 2013. Based on these surveys, following conclusions were obtained: In four coastal beaches surveyed, the mean number and weight densities were 25.91 items/100m2 and 341.39 g/100m2, respectively. Most of the BMD in the aforementioned beaches originated directly from land sources. There were two kinds of debris collection systems in these beaches at present; dustbins sometimes were not enough to be used in the swimming period.We hope that our study will be helpful to raise the level of environmental consciousness among people and to expand their anti-debris activities.